National Steinbeck Center - Jerome Kasavan and Thompson Vaivoda Associates (sketch):::Creator::::::::::::
National Steinbeck Center (NSC, 1 Main Street) sketches by Jerome Kasavan and Thompson Vaivoda Associates. From series of publicity shots. Slide only.